THE ROLE OF COMPLIMENT ON THE BUY-SELL TRANSACTION AT TRADITIONAL MARKET - ALFANI, FAHMI REZA; SUKARNO, SUKARNO; HARYONO, AKHMAD (TELL - US JOURNAL, 2021)
AbstractThe compliment has the important role to the communication because it could give a happy effect for the speaking partner. In the interaction context, the compliment often used as the communication strategy to achieve the particular interest. The compliment has the important role in the buy-sell transaction in the traditonal market. This research aims to describe the important role of the compliment on the success of the buy-sell transaction in the traditional market. This research used qualitative descriptive to analize the compliment used by seller and buyer. The data were collected through conversation using a hidden recorder and taking some notes. The result of the study showed that the compliment has the four roles on the success of buy-sell transaction in the traditional market such as at Pasar Waru, Kabupaten Sidoarjo. Those were the comliment as caller the buyer, the tool of the bargaining, to convincing the buyer, and the small talk. Keywords: compliment, communication strategy, buy-sell transaction